Malaria and anemia prevention in pregnant women of rural Burkina Faso - Jahn Albrecht; Kouyate Bocar; Some Florent; Miaffo Caroline; Mueller Olaf (BMC, 2004)
Abstract Background Pregnant women are a major risk group for malaria in endemic areas. Only little information exists on the compliance of pregnant women with malaria and anaemia preventive drug regimens in the rural areas of sub-Saharan Africa (SSA). In this study, we collected information on malaria and anaemia prevention behaviour in pregnant women of rural Burkina Faso. Methods Cross-sectional qualitative and quantitative survey among 225 women of eight villages in rural northwestern Burkina Faso. Four of the villages had a health centre offering antenatal care (ANC) services while the other four were more than five kilometers away from a health centre. Results Overall ANC coverage (at least one visit) was 71% (95% in health centre villages vs 50% in remote villages). Malaria and anaemia were considered as the biggest problems during pregnancy in this community. ANC using women were quite satisfied with the quality of services, and compliance with malaria and anaemia prevention regimens (chloroquine and iron/folic acid) was high in this population. Knowledge on the benefit of bed nets and good nutrition was less prominent. Distance, lack of money and ignorance were the main reasons for women to not attend ANC services. Conclusions There is an urgent need to improve access of rural SSA women to ANC services, either through increasing the number of rural health centres or establishing functioning outreach services. Moreover, alternative malaria and anaemia prevention programmes such as intermittent preventive treatment with effective antimalarials and the distribution of insecticide-treated bed nets need to become implemented on a large scale.